Answer: 6x+18/(-x²+6x-5)
Step-by-step explanation:
• f is not defined at 1
• f(−3) = 0
• f(3) = 9
• lim x→5+ f(x) = −[infinity]
• lim x→5− f(x) = [infinity]
• f is not defined at 1
we need to have a denominator 0 for x = 1
so, 1/(x-1)
• lim x→5+ f(x) = −[infinity]
• lim x→5− f(x) = [infinity]
For the limits, we need to have
1/(-x+5)
this way, lim x→5+ f(x) = −[infinity] and lim x→5− f(x) = [infinity]
So far we have
1/(x-1)(-x+5)
• f(−3) = 0
the nominator has to be 0 when x = -3
this way, x+3
so, (x+3)/(x-1)(-x+5)
• f(3) = 9
All we need to do is multiply (x+3)/(x-1)(-x+5) by 6, so
6(x+3)/(x-1)(-x+5) = 6x+18/(-x²+6x-5)